ACTANT GREIMAS STRUCTURE NARRATIVE ON THE COLOR PURPLE BY ALICE WALKER - Dalpah; Nargis; Eka Ugi Sutikno (UIN Alauddin Makassar, 2025)
This study examines the narrative structure of Alice Walker's “The Color Purple” through the lens of Greimas' actant model. Therefore, the purpose of this study is to apply the narrative structure with Greimas' actant model to enable a comprehensive analysis of how the main character, Celie, experiences a journey of transformation from oppression to personal freedom using Greimas' actant theory. With this, the focus of the problems that arise in this study are: (1) what are the actant schemes that can be found in the novel “The Color Purple?” (2) How does the actant Greimas describe the journey of transformation of the main character in the novel “The Color Purple?” By using descriptive qualitative research method. Data collection in this study focuses on the novel “The Color Purple” by Alice Walker as the main data source. For data analysis, qualitative analysis is used, the process of which is carried out through the stages of data analysis, data presentation, and conclusion drawing. The dynamic interaction between actants reflects the systemic nature of trauma and how liberation is built through family relationships, faith, and love. By mapping Celie's journey through Greimas' actant model, the novel “The Color Purple” is not only a personal narrative, but also a structurally complex story of transformation. Each actant role develops along with Celie, reflecting how freedom and identity are achieved not through isolation, but through enduring relationships, personal growth, and ultimately overcoming oppression.